Unraveling oxygen vacancy-driven catalytic selectivity and hot electron generation on heterointerfaces using nanostructured platform - Gyu Rac Lee; Kyoungjae Song; Doosun Hong; Juyoung An; Yujin Roh; Minyoung Kim; Donghun Kim; Yeon Sik Jung; Jeong Young Park (Nature Communications)
Abstract Modulating the physicochemical properties of oxides is crucial to achieve efficient and desirable reactions in heterogeneous catalysis. However, their catalytic role is not clearly identified because unevenly distributed interfaces and close conjugation with metal catalysts may hinder distinguishing their contribution in complex random structures. Here, we demonstrate a model platform composed of well-aligned CeOx nanowire arrays on Pt catalysts to observe their catalytic role systematically. Independently modulating the crystallinity and oxygen vacancy concentration of oxide nanowires, while preserving heterogeneous interfaces, enables quantitative analysis of their individual effects on partial oxidation selectivity, resulting in hot electron generation during methanol oxidation reactions. CeOx treated with vacuum annealing on Pt exhibits 1.47- and 2.12-times higher selectivity to methyl formate and chemicurrent yield than CeOx without annealing on Pt. Density-functional theory calculations reveal that the promoted charge transfer from the electron-accumulated interface driven by oxygen vacancy acts as a key parameter in enhancing selectivity.